The Formation of the Identities of Contemporary Youth - Joel Luis Dumke (Universidade Estadual Paulista Júlio de Mesquita Filho, 2013)
This is a theoretical study which has as its goal the discussion of the formation of the identities of the youth in contemporary society. The article understands that the formation of the identities of the youth takes place in social, cultural and historical contexts, and thus, it is necessary to do a reading of youth in the plural, since there is no one type of youth, but there are heterogeneous youth which are constructed in the midst of daily relations, including the school space. Taking this into account, the article understands the school to be a an important space for the formation of the identities of human beings, when the school respects the culture and life of those being educated. The respect for the subject and the postures adopted by the teachers are emphasized in the works of Paulo Freire entitled Medo e Ousadia [Fear and Audacity] and the Pedagogy of the Oppressed, where the author dicusses the importance of dialog for the formation of the subjects and how damaging the school bench model is. The article ends the discussion on the importance of a dialogic posture in the construction of the identities of learners proposing a reflection about the caring administration. This is about an educational proposal which is open to diversities, which understands the students in a wholistic, affectionate, fraternal way and where dialog is understood as an ontological requirement and not as a teaching technique or some type of manipulation mechanism.